One night of sleep deprivation impairs executive function but does not affect psychomotor or motor performance - Skurvydas, Albertas; Zlibinaite, Laura; Solianik, Rima; Brazaitis, Marius; Valanciene, Dovile; Baranauskiene, Neringa; Majauskiene, Daiva; Mickeviciene, Dalia; Venckunas, Tomas; Kamandulis, Sigitas (Biology of Sport, 2020)
The current study assessed the impact of one night of sleep deprivation on cognitive, motor and psychomotor performance. Thirty healthy young adult male subjects completed a 24 h control or 24 h sleep deprived trial. For the control trial, participants (N = 15) were allowed normal night sleep (~8 h). For the sleep deprived trial, participants (N = 15) did not sleep for 24 h. Cognitive performance during go/no-go, Stroop and simple reaction tasks, psychomotor performance during speed-accuracy tasks with fixed and unfixed targets, and motor performance during countermovement jump, hand grip strength, and 30-s maximal voluntary contraction tasks were evaluated on day 1 at 8 am and 7 pm and on day 2 at 8 am. One night of sleep deprivation impaired psychological well-being and executive function but did not affect simple reaction time, the capacity for arm and leg muscle contraction, motor control performance during a speed–accuracy task with both fixed and unfixed targets, and central and peripheral motor fatigue in the 30 s maximal voluntary contraction task. The present study showed that one night of sleep deprivation resulted in executive function deterioration but did not modify motor control or maximal effort requiring performance of motor tasks